Electrical power transmission system engineering analysis and design - Gönen, Turan (CRC Press, Taylor and Francis Group, 2014)
Electrical Power Transmission System Engineering: Analysis and Design is devoted to the exploration and explanation of modern power transmission engineering theory and practice. Designed for senior-level undergraduate and beginning-level graduate students, the book serves as a text for a two-semester course or, by judicious selection, the material may be condensed into one semester. Written to promote hands-on self-study, it also makes an ideal reference for practicing engineers in the electric power utility industry